FRI0610-HPR Β-ADRENORECEPTOR BLOCKING DRUGS ASSOCIATE WITH LOWER RISK OF KNEE OSTEOARTHRITIS AND KNEE PAIN CONSULTATIONS IN PRIMARY CARE: A PROPENSITY SCORE MATCHED COHORT STUDY USING THE CLINICAL PRACTICE RESEARCH DATALINK. (2nd June 2020) - Nakafero, G.; Grainge, M.; Valdes, A.; Townsend, N.; Mallen, C.; Zhang, W.; Doherty, M.; Mamas, M.; Abhishek, A.
Abstract : Background: The pharmacologic management of OA is centred around optimising pain control but first-line analgesics only have modest efficacy 1 . Findings from several studies suggest that β -adrenoreceptor blocking drugs ( β -blockers) have anti-nociceptive effects 2 3 . However, evidence for the benefits of β-blockers in the context of OA pain is scarce. We recently demonstrated, for the first time, an association between beta-blockers and lower pain severity, and less opioid analgesic use in a secondary analysis of data for community dwelling adults with large-joint lower OA 4 . This association, however, was not confirmed in a hospital-based study 5 . Objectives: We examined [1] the association between β -blocker prescription and first primary care consultation for knee OA, hip OA, knee pain, and hip pain and [2] the classes of β -blocker drugs that reduce the risk of these outcomes. Methods: This was a cohort study using data from the UK Clinical Practice Research Datalink. Participants aged ≥40 years, in receipt of ≥2 β-blocker prescriptions within 60 days were matched by age, sex, and propensity score (PS) for β-blocker prescription to one control using greedy nearest neighbour matching. Participants with chronic painful conditions, contra-indications to β-blockers, maintenance analgesic prescriptions, and with <2-years registration before index or matched follow-up start date were excluded. Cox proportional hazard ratios (aHRs) and 95% confidence intervals (CI) were calculated to examine the associations adjusted for other covariates. Analyses were stratified according to β-blocker classes. Results: Data for 223, 436 PS-matched exposed and un-exposed participants were included. β-blocker prescription associated with a significantly reduced risk of knee OA, knee pain, and hip pain consultations with aHR(95%CI) 0.90(0.83–0.98), 0.88(0.83–0.92), 0.85(0.79–0.90) respectively. The reduction in hip OA lacked statistical significance (aHR 95%CI 0.94; 0.83-1.07) (Table 1 ). On stratified analysis, propranolol and atenolol had a statistically significant protective effect on knee OA and knee pain consultations with aHRs between 0.78 and 0.91 (Figure 1 ). Conclusion: β-blockers appear to reduce consultations for knee OA, and knee or hip pain. Our results imply that, atenolol might be used preferentially for the treatment of people with cardiovascular comorbidities, while, propranolol with its' anti-anxiety effect may be a suitable analgesic in people with OA and comorbid anxiety. References: [1] McAlindon TE, et al. Osteoarthritis and Cartilage 2014;22(3):363-88. [2] Harkanen L, et al. Journal of anesthesia 2015;29(6):934-43. doi: 10.1007/s00540-015-2041-9 [3] Light KC, et al. The journal of pain 2009;10(5):542-52. doi: 10.1016/j.jpain.2008.12.006 [4] Valdes AM, et al. Arthritis Care Res (Hoboken) 2017;69(7):1076-81. doi: 10.1002/acr.23091 [5] Zhou L, et al. Osteoarthritis and Cartilage 2019 doi: https://doi.org/10.1016/j.joca.2019.08.008 Acknowledgments: This work was funded by the National Institute for Health Research (grant numbers: PB-PG-0816-20025 and NIHR-RP-2014-04-026). Disclosure of Interests: Georgina Nakafero: None declared, Matthew Grainge: None declared, Ana Valdes Grant/research support from: Pfizer Inc, Consultant of: Consultant for Heel GmBH, Nick Townsend: None declared, Christian Mallen Grant/research support from: My department has received financial grants from BMS for a cardiology trial., Weiya Zhang Consultant of: Grunenthal for advice on gout management, Speakers bureau: Bioiberica as an invited speaker for EULAR 2016 satellite symposium, Michael Doherty Grant/research support from: AstraZeneca funded the Nottingham Sons of Gout study, Consultant of: Advisory borads on gout for Grunenthal and Mallinckrodt, Mamas Mamas: None declared, Abhishek Abhishek Consultant of: Consulting for Inflazome, and Royalties from Uptodate and Springer